1986
DOI: 10.1042/bj2390717
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of a cDNA and assignment of the C-terminal of sarcotoxin IA, a potent antibacterial protein of Sarcophaga peregrina

Abstract: A previous paper described the complete amino acid sequences of sarcotoxins IA, IB and IC, which are a group of potent antibacterial proteins with almost identical primary structures produced by Sarcophaga peregrina (fleshfly) larvae [Okada & Natori (1985) J. Biol. Chem. 260, 7174-7177]. The present paper describes the cDNA cloning and complete nucleotide sequencing of a cDNA clone for sarcotoxin IA. The C-terminal amino acid residue of sarcotoxin IA deduced from the nucleotide sequence was glycine, whereas it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(38 citation statements)
references
References 29 publications
1
37
0
Order By: Relevance
“…We assigned the signal sequence of this enzyme as 20 amino acid residues from the first Met to Ala at position 20, because this region is hydrophobic, as shown in Fig. 2, and the carboxyl terminal amino acid residues of the signal sequences of all secretory proteins of Sareophaga so far examined are Ala [13,14]. Thus the pro-segment of this enzyme may be the 67 amino acid residues from position 21 to 88.…”
Section: Sized As Ga(tic)gticciga(aig)ga(aig)tt(tic)ga(tic)gcmentioning
confidence: 99%
“…We assigned the signal sequence of this enzyme as 20 amino acid residues from the first Met to Ala at position 20, because this region is hydrophobic, as shown in Fig. 2, and the carboxyl terminal amino acid residues of the signal sequences of all secretory proteins of Sareophaga so far examined are Ala [13,14]. Thus the pro-segment of this enzyme may be the 67 amino acid residues from position 21 to 88.…”
Section: Sized As Ga(tic)gticciga(aig)ga(aig)tt(tic)ga(tic)gcmentioning
confidence: 99%
“…Furthermore, the measured mass compared to the predicted mass (4060.6 Da) from the amino acid sequence, eliminated any possibility of post-translational modifications involving variations of more than 1 Da. A monoisotopic mass measurement (measured, 4057.90 Da; expected, 4057.81 Da) with an accuracy better than 0.1 Da was also achieved [l] and it was thus possible to demonstrate that the C-terminus was not amidated (expected mass difference of -1 Da) although this has been described for other antibacterial peptides like cecropin isolated from Hyalophora cecropia [2] and the related sarcotoxin IA isolated from Sarcophaga peregrina [3], as well as diptericin isolated from P. terranovae [4]. Finally, the data obtained from mass spectrometry measurements also showed that natural insect defensin A was not present in a covalent dimeric form since the molecular ion did not exhibit peaks separated by mjz 0.5, and no peak was detected at mjz 8120 [l].…”
Section: ---mentioning
confidence: 99%
“…Working alongside Dr. Zong-Qu Li (a visitor from the University of Wuhan, in China), we prepared both precursors and their putative downstream products in suitably labeled forms that allowed to study their posttranslational processing in considerable detail. 9 By then, other laboratories, mainly Lehrer's at UCLA, 10 Shunji Natori's in Tokyo [11][12][13] …”
mentioning
confidence: 99%
“…Working alongside Dr. Zong-Qu Li (a visitor from the University of Wuhan, in China), we prepared both precursors and their putative downstream products in suitably labeled forms that allowed to study their posttranslational processing in considerable detail. 9 By then, other laboratories, mainly Lehrer's at UCLA, 10 Shunji Natori's in Tokyo [11][12][13] 14 had discovered similar antimicrobial activities in biological systems other than Boman's Cecropia moth, and in several cases applied synthetic peptide chemistry to explore mechanisms of action and to develop analogues with improved properties. The field of antimicrobial peptide research was taking off to become one of the most dynamic areas of peptide-related research over the next decades.…”
mentioning
confidence: 99%
See 1 more Smart Citation